Design optimization and structural assessment of a header and coil steam generator for load-following solar tower plants. (June 2022) - González-Gómez, P.A.; Laporte-Azcué, M.; Fernández-Torrijos, M.; Santana, D.
Abstract: The aim of this work is to explore the capabilities, from heat transfer and structural point of view, of a novel header and coil steam generator for a 100 MWe solar tower plant using molten-salt as heat transfer fluid. A methodology for the design and economic optimization of the header and coil steam generator is presented, paying special attention to the structural assessment which considers complex phenomena such creep-fatigue and stress relaxation due to the high working temperatures of solar tower plants. The results showed that header and coil steam generators provide economically effective overall heat transfer coefficients with lower pressure drops on the shell side compared to conventional shell-and-tube steam generators, leading to a reduction in the annual pumping costs of around 3.6 times. The structural assessment reveals that the critical points are located in the headers of superheater, reheater and evaporator. Different redesign actions have been performed to increase the lifetime in the critical points without affecting to the optimum thermo-economic solutions. Finally, the results showed that the header and coil steam generator is able to operate with fast daily startups at 6.1 K/min, a ramp-up 2.4 times higher than conventional shell-and-tube steam generators.